Analisis Kesantunan Berbahasa dalam Daftar Putar Satu Persen Taman Edukasi: Career Preparation - Ardelia Inez Maharani; Jely Mila Ashari; Arif Mansurrudin; Mei Purweni; Hanum Sa’ada Fidaroeni; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Within language, there are several categories, such as language politeness, which have objectives and intents that vary depending on the context and situation of human communication. In this language civility study, attention is drawn to the goals and intentions generally contained in our language usage. This study aims to identify forms of compliance and violations of the principle of language politeness on the Satu Persen playlist of Taman Edukasi: Career Preparation. This research uses two approaches, namely the qualitative descriptive approach as a methodological approach and the pragmatic approach as a theoretical approach. The technique used in collecting data is the listen-and-record technique. Data analysis of this research is presented through a data triangulation process, which includes three stages: data verification, data presentation, and data classification. The author conducted this research hoping that public knowledge about the principles of language politeness will be wider. This study aims to identify forms of compliance and violations of the principle of language politeness on the Satu Persen playlist of Taman Edukasi: Career Preparation. The results showed that in the playlist there were thimbles of generosity, wisdom, consensus, opinion, and sympathy thimbles. However, there is no thimble of apology, forgiveness, appreciation, simplicity, and feeling. Furthermore, the study's findings demonstrate the necessity for an increased awareness of the utilization of courteous and deferential language in communication, particularly concerning the realm of education and career readiness.